HIV/AIDS occupational exposure and integrative care; knowledge, attitude, and skills of healthcare workers in Gansu Province, China - Mundra, Leela S.; Aslam, Sadaf; Zhang, Juxia; Lin, Han; Xu, Peng; Morano, Jamie (International Journal Of Community Medicine And Public Health, 2017)
Background: For HIV infected patients, distinct infectious disease hospitals currently exist in China, therefore, attitudes promoting separation within health care settings persist both in healthcare workers and community. The misinformation and fear of infection negatively affect Health Care Workers, (HCWs) attitudes towards caring for patients with HIV. However, the level of knowledge, attitudes, and skills (KAS) towards occupational exposure to HIV and post-exposure standards of care are unknown in Gansu, China. Methods: We conducted a cross-sectional study to evaluate the knowledge, attitudes, and skills of health care workers regarding HIV occupational exposure and treatment. We analyzed findings in a total of 324 HCWs through a self-reported questionnaire. Results: HCWs with a higher than average KAS composite score compared to HCWs with a lower KAS score were more likely to be working clinically (p=0.0023), and had completed a university degree or above (p=0.0370). The univariate analysis model also showed additional factors that HCWs having a higher KAS composite score were significantly associated with being a physician (OR 9.22; p=0.045) and receiving formal infection control training (OR 4.20; p<0.0001). Conclusions: Our study provides considerable information on occupational exposure regarding HIV/AIDS in Gansu Province of China. A continuous education is necessary to increase the level of knowledge, attitude and skills of HCWs about the risk of infection at the workplace. With the adoption of standardized occupational exposure protocols and infection control programs, we should be able to reduce barriers of HIV care into general hospital facilities which in turn can modify their attitudes.